Fetal Effects of Combined Spinal-Epidural Versus Epidural Labor Analgesia. Issue 2 (June 2015) - Patel, N.P.; El-Wahab, N.; Fernando, R.; Wilson, S.; Robson, S.C.; Columb, M.O.; Lyons, G.R.
<x xml:space="preserve">Abstract</x> (Anaesthesia. 2014;69(5):458–467)